PENGARUH WAKTU FERMENTASI TERHADAP KANDUNGAN NITROGEN, FOSFAT, DAN KALIUM PADA PUPUK ORGANIK DARI LIMBAH BAGLOG JAMUR TIRAM PUTIH DAN GUANO - Nufus, Wahyu Qur'ani; Nuraini, Adila Silmi; Suprianti, Lilik; Perwitasari, Dyah Suci; Wahyudi, Bambang (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This study aims to evaluate the fermentation process of white oyster mushroom baglog waste and bat guano as materials for producing multi-nutrient fertilizer, and to determine the optimal fermentation time that yields the highest levels of nitrogen, phosphate, and potassium by the 2019 Ministry of Agriculture standards. An anaerobic fermentation process was employed using white oyster mushroom baglog waste and bat guano as the primary materials, supplemented with an EM-4 bioactivator to accelerate decomposition. Fermentation was conducted over 20 days and was checked every 4 days. The research results indicate that fermentation time influences the nutrient content of the produced fertilizer. The highest nitrogen content of 2.81% was achieved on the 16th day of fermentation, while the highest phosphate content of 2.28% was recorded on the 8th day of fermentation. The highest potassium content of 3.59% was reached on the 16th day of fermentation. Based on these findings, a fermentation period of 16 days provided optimal results for nitrogen and potassium content, whereas an 8-day fermentation period yielded optimal results for phosphate content.